Evaluasi Penerapan Good Corporate Governance Terhadap Program Kerja Komunitas Sablon Jombang - Hendrawan, Fieri; Sholafudin, Fais; Djasuli, Mohamad (CV. ITTC INDONESIA, 2023)
This study used a qualitative methodological approach with data collection techniques using face-to-face interviews with the head of the Jombang screen printing community. Good Corporate Governance (GCG) is a management process that is an important part of the company's operations to achieve the goal of a healthy society. GCG application is considered important during the economic crisis in Indonesia, so it is necessary to ensure the safety of investor capital. There are also government requirements and support for Indonesian companies to implement GCG principles in their operations. This research was conducted in Jombang to examine the application of GCG principles such as transparency, accountability, responsibility, independence and fairness in screen printing. Interviews and observations are used as data collection methods. Sampling is intended to be used to identify interviewees by examining samples from data sources on different and relevant topics. The results of this study are that the company applies the principles of transparency, accountability, responsibility, independence and honesty, which are the basis of good corporate governance (GCG), although not fully in accordance with GCG provisions. principle. . It is hoped that the company will continue to implement policies and continue to implement policies that have not been fully implemented.